Carbon-based catalysts for methanol production by CO2 hydrogenation. - Jiménez-Gómez, María del Rocío; Ruiz-Rosas, Ramiro Rafael; Rosas-Martínez, Juana María; Rodríguez Mirasol, José; Cordero-Alcántara, Tomás (My University, 2025)
The hydrogenation of CO₂ captured represents a promising and sustainable pathway for the production of renovable methanol. The use of carbon nanofibers (CFs) as catalytic support can solve some of the drawbacks of methanol synthesis in fixed bed reactors. Cu/ZnO/carbon nanofibers catalysts were prepared using electrospinning technique of a lignin-based solution, followed by thermal treatment (stabilization and carbonization).
Keywords: Fibra de carbono; Metanol (combustible); CO2; H2; Metanol; Fibras